Análisis del empleo de las herramientas de aprendizaje virtual (Journal on studies and research of academic knowledge, 2019)
ICTs are becoming more relevant as a result of the international epidemiological situation generated by COVID-19. The results presented are a consequence of the interest in deepening one of the edges of the use of information and communication technologies in higher education. In this sense, an analysis has been made of the importance of the use of new virtual learning tools for teaching at university. To this end, surveys were conducted among professors of the Industrial Engineering career at the Universidad Americana de Asunción. Emphasis was placed on the transformations caused by virtualization in the teaching staff for its implementation. In addition, the hours dedicated for the assimilation of these were taken into consideration, as well as the usefulness that, in their opinion, they could have for the present and future of teaching and learning at the higher educational level.
Keywords: higher education; ICT; digital tools; industrial engineering